Evaluating the Performance Measurement System (PMS) in the financial service industry in a developing country: the case of Bangladesh / MAA Mahbubul Islam and Noel Yahanpath - Islam, MAA Mahbubul; Noel, Yahanpath (Accounting Research Institute (ARI), 2013)
The aim of the paper is to investigate the application of financial and nonfinancial performance measures (value drivers) in the financial service industry in Bangladesh and their linkage to future financial outcomes and a firm’s strategy. Data was obtained from 73 respondent firms and a descriptive analysis was used. We found that the financial service industry in Bangladesh is still very much reliant on financial performance measures rather than non-financial performance measures. However, the trend of using non-financial performance measures is increasing. We also found that there is a relationship between the use of non-financial performance measures and the resultant future financial outcomes. Moreover, a linkage was found between a firm’s use of different performance measures and its strategy.